Synthesis and Biological Activities of Some New Formazans, Part-I - Bharadwaj, S.D. (Asian Journal of Chemistry, 2010)
1-(Phenyl-3-(2-methoxy-4-N,N´-bis-2´-cyanoethylamino phenyl-p-tolyl formazans have been synthesized by first reacting 4-N,N´-bis-2-cyanoethylamino-2-methoxy benzaldehyde withp-tolyl hydrazide which gave the acid hydrazone. The acid hydrazone on treatement with diazotised aromatic amines in pyridine mediwn furnished fifteen formazans in 40 to 54% yield. The acid hydrazone and the formazans were found to be devoid of anticancer and anti-HIV activities.